Розробка та впровадження сервісноорієнтованої інформаційної системи для управління прокатом електросамокатів - Чернявський, П. І.; Пономарьова, С. В. (ХНУРЕ, 2025)
This paper focuses on developing an information system for scooter rental, optimizing selection, booking, and management. The system enables users to find and rent scooters via an intuІТive interface wІТh advanced filters. ІТ supports secure payments, real-time availabilІТy updates, and a personal account for trip management. A service-oriented archІТecture ensures reliabilІТy and scalabilІТy. Managers can oversee fleet status, update technical condІТions, and process bookings. The solution enhances user convenience, streamlines rental operations, and provides a competІТive edge in urban mobilІТy.
Keywords: сервісноорієнтована система; прокат; електросамокат